Simple Model for Respiratory Diseases - Puntani Pongsumpun (My University, 2017)
Respiratory diseases can easily transmit between people.In this study, we formulate the simple model S-I-R-I (Susceptible-Infectious-Recovered-Infectious) for describing the transmission of this disease.The model is analyzed by using dynamical modeling method.After that, we simulate our equations by using numerical method.The numerical solutions are found to confirm our analytical results.Analysis of parameters are given.
Keywords: Zoonotic diseases and public health